Electrocatalytic water oxidation by a water-soluble copper complex with a pentadentate amine-pyridine ligand. Issue 31 (26th July 2021) - Xu, Ziyi; Zheng, Zilin; Chen, Qi; Wang, Jiayi; Yu, Kaishan; Xia, Xin; Shen, Junyu; Zhang, Qijian
Abstract : A water-soluble copper complex bearing a pentadentate N5 ligand works as an efficient and stable electrocatalyst for the water oxidation reaction in basic aqueous solution. Abstract : A water-soluble copper complex with a diamine-tripyridine ligand was synthesized successfully and well characterized. It was found to be catalytically active for the water oxidation reaction under basic conditions. Based on the electrochemical test result, this copper complex displayed an apparent rate constant ( k cat ) of 0.81 s −1 for the oxygen evolution reaction in 0.1 M phosphate buffer solution at pH 11.0. More importantly, the copper complex remained stable over 3 h of a bulk electrolysis experiment at 1.60 V with a Faradaic efficiency of 90.7% for O2 evolution, and the decrement of current density was only 1.9%. These results suggest that the pentadentate copper complex is an efficient and durable homogeneous Earth-abundant electrocatalyst for water oxidation.